THE DEVELOPMENT OF ALGORITHMS FOR CALCULATING THEORETICAL- NUMERICAL SIGNAL TRANSFORMATIONS WITH THE LEAST NUMBER OF MULTIPLICATIONS - M. I. Kalmykov; D. V. Yurdanov; I. A. Kalmykov; I. D. Efremenkov (Современная наука и инновации)
When using a discrete Fourier transform (DFT) to solve digital signal processing (DSP) problems, errors occur in rounding or truncating the results of operations to the word length used by specialized processors (SP). These errors occur in the paths for calculating the real and imaginary parts of the signal. In finite rings and Galois fields, a transformation can be defined whose properties are isomorphic to the properties of DPF and the Search for new ways to improve the efficiency of digital signal processing has led to the activation of the development of mathematical models that have the properties offinite algebraic structures.